Helicobacter pylori 23S rRNA gene mutations associated with clarithromycin resistance in chronic gastritis in Vietnam - Van Huy Tran; Thi Minh Thi Ha; Phan Tuong Quynh Le; Viet Nhan Nguyen; Trung Nam Phan; Bianca Paglietti (Journal of Infection in Developing Countries)
Introduction: Data about the prevalence of the A2142C, A2142G, and A2143G mutations in 23S rRNA gene is still limited. The aim of this study was to determine the prevalence of these mutations in 23S rRNA gene of H. pylori vietnamese strains.